State of the Art in Congenital Eyelid Deformity Management - Lin, Lily Koo; Martin, Jonathan (Facial Plastic Surgery, 2016)
The eyelids are crucial in maintaining the health of the ocular surface and have an important role in facial aesthetics. Interruption in eyelid development can lead to congenital eyelid deformities. This article reviews eyelid anatomy, the most common congenital eyelid abnormalities such as congenital ptosis, eyelid coloboma, and epiblepharon, and the management of these conditions.
Keywords: congenital ptosis; eyelid coloboma; epiblepharon